HAC++: Towards 100X Compression of 3D Gaussian Splatting - Chen, Yihang; Wu, Qianyi; Lin, Weiyao; Harandi, Mehrtash; Cai, Jianfei (IEEE transactions on pattern analysis and machine intelligence, 2025)
3D Gaussian Splatting (3DGS) has emerged as a promising representation for novel view synthesis, boosting rapid rendering speed with high fidelity. However, the substantial Gaussians and their associated attributes necessitate effective compression techniques. Nevertheless, the sparse and unorganized nature of the point cloud of Gaussians (or anchors in our paper) presents challenges for compression. In this paper, we propose HAC++, which explicitly minimizes the representation's entropy during optimization, enabling efficient arithmetic coding after training for compressed storage. Specifically, to reduce entropy, HAC++ leverages the relationships between unorganized anchors and a structured hash grid, utilizing their mutual information for context modeling. Additionally, HAC++ captures intra-anchor contextual relationships to further enhance compression performance. To facilitate entropy coding, we utilize Gaussian distributions to precisely estimate the probability of each quantized attribute, where an adaptive quantization module is proposed to enable high-precision quantization of these attributes for improved fidelity restoration. Moreover, we incorporate an adaptive masking strategy to eliminate non-effective Gaussians and anchors. Overall, HAC++ achieves a remarkable size reduction of over 100× 100×<inline-graphic xlink:href="lin-ieq1-3594066.gif"/> compared to vanilla 3DGS when averaged on all datasets, while simultaneously improving fidelity. It also delivers more than 20× 20×<inline-graphic xlink:href="lin-ieq2-3594066.gif"/> size reduction compared to Scaffold-GS.